Heteroatom sulfur-induced defect engineering in carbon nanotubes: Enhanced electrocatalytic activity of oxygen reduction reaction - Fan, Haiyun; Wang, Tao; Gong, Hao; Jiang, Cheng; Sun, Zhipeng; Zhao, Manman; Song, Li; He, Jianping (Carbon (New York), 2021)
Heteroatoms doped carbon nanotubes are prepared through a solid-state pyrolytic conversion strategy with low-cost and easy-to-get precursors. The use of inorganic sulfur source makes it possible for sulfur to be effectively introduced, which is found to increase the defective degree in the carbon plane. The defect augment is revealed by systematic physical characterizations to originate from the fact that S atoms get rid of the carbon crystal and diffuse to form bits of sulfides during the heat-treatment process, thus leaving abundant vacant spots and providing access to forming pyridine-N sites. Therefore, more catalytic active sites are exposed and the oxygen reduction reaction (ORR) activity can be improved. Benefiting from the advantages in structure and composition, the resultant catalyst shows a remarkable half-wave potential (0.86 V vs. RHE) and an outstanding durability, superior to that of Pt/C. The zinc-air battery with the resultant catalyst shows high peak power density and excellent rate capability. This work not only develops a facile method to prepare highly active and stable ORR catalyst but also makes deep researches on the activity-enhanced mechanism. [Display omitted] •A facile and scale-up method was developed for the synthesis of N, S-enriched carbon nanotubes.•The introduction of S atom induces the carbon defects, leading to activity enhancement in the carbon nanotube.•The transfer of S atom during the heat-treatment process leaves abundant vacant spots for generating pyridine-N sites.•The catalyst exhibits a prominent ORR activity and an outstanding durability, superior to Pt/C.